2021
DOI: 10.1186/s12989-021-00406-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to diesel exhaust may cause small airway wall thickening without lumen narrowing: a quantitative computerized tomography study in Chinese diesel engine testers

Abstract: Background Diesel exhaust (DE) is a major source of ultrafine particulate matters (PM) in ambient air and contaminates many occupational settings. Airway remodeling assessed using computerized tomography (CT) correlates well with spirometry in patients with obstructive lung diseases. Structural changes of small airways caused by chronic DE exposure is unknown. Wall and lumen areas of 6th and 9th generations of four candidate airways were quantified using end-inhalation CT scans in 78 diesel eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Numerous studies have demonstrated the significant induction of proinflammatory cytokines in diabetes patients; moreover, diabetic retinopathy is the most common microvascular complication of diabetes and the leading cause of retinopathy [ 47 ]. In addition, PM2.5 induces inflammation and cell death in human trabecular meshwork cells to trigger ocular hypertension and glaucoma [ 48 ]. Given these previous findings, we chose to assess proinflammatory cytokine levels and found that RPE cells exposed to PM2.5 showed a large increase in the secretion of IL-6 and TNF-α, which are both associated with retinopathy [ 27 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated the significant induction of proinflammatory cytokines in diabetes patients; moreover, diabetic retinopathy is the most common microvascular complication of diabetes and the leading cause of retinopathy [ 47 ]. In addition, PM2.5 induces inflammation and cell death in human trabecular meshwork cells to trigger ocular hypertension and glaucoma [ 48 ]. Given these previous findings, we chose to assess proinflammatory cytokine levels and found that RPE cells exposed to PM2.5 showed a large increase in the secretion of IL-6 and TNF-α, which are both associated with retinopathy [ 27 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al showed that long-term exposure to ambient PM 2.5 or black carbon correlated significantly with computed tomographic defining emphysema in adults [ 32 ]. Liu et al suggested that chronic exposure to diesel exhaust may be related to small airway wall thickening in diesel engine testers [ 33 ]. In the present study, we confirmed the causal effects of DEP exposure on small airway remodeling as well as lung emphysema and associated lung function impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have reported a higher incidence of asthma among children in high DEE exposure areas, as well as a higher frequency of hospitalization for asthma and COPD exacerbation among long-term DEE-exposed populations [ 27 , 28 , 29 ]. Our prior study revealed that small airway walls were significantly thickened in the workers under chronic exposure to diesel exhaust [ 30 ]. In this study, we found that mice exposed to DEE developed airway epithelial damage, airway smooth muscle hyperplasia, and excessive peribronchial collagen deposition, which was accompanied by worse respiratory parameters (reduced respiratory flow rate, tidal volume, airway relaxation time, etc.).…”
Section: Discussionmentioning
confidence: 99%